Relationship between Human Resource Management Practices and High-Performance Outcomes in Financial Institutions - Pradhan, Gopal Man; Shrestha, Prakash (Journal of Business and Social Sciences, 2023)
The foundation of this study is the effect that HRM strategies have on the high-performance outcomes of financial institutions in Nepal, as measured by organizational performance. While productivity, quality, and innovation are variables of high-performance outcomes, recruitment and selection, training and development, performance appraisal, career planning, remuneration, employee participation, and job design are variables of HRM practices. The job design in this study has a significant sensitivity to organizational success in terms of high-performance, followed by employee participation and remuneration structure, according to an analysis of the beta coefficient. However, every other factor including career planning, training and development, and recruiting and selection has a favorable effect on the high-performance results of organizational performance. However, the impact of career planning, training and development, and recruiting and selection on high-performance outcomes is negligible. This research work suggested that to improve the performance levels of financial institutions, it is essential to invest sufficient funds for completing HRM practices, based on the scope of business.